2009
DOI: 10.1007/s00420-009-0417-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting long-term sickness absence and early retirement pension from self-reported work ability

Abstract: Reports of reduced work ability were significantly associated with both an increased risk of onset of LTSA and early retirement from the labour market, after adjustment for socio-demographic characteristics and lifestyle variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
103
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(114 citation statements)
references
References 19 publications
7
103
2
2
Order By: Relevance
“…Our findings concerning the significance of WAI in relation to disability retirement are in line with several previous reports (3,4,26,27). Among the studies on both WAI and WAS predating disability retirement, ours is the first to use longitudinal data on work ability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings concerning the significance of WAI in relation to disability retirement are in line with several previous reports (3,4,26,27). Among the studies on both WAI and WAS predating disability retirement, ours is the first to use longitudinal data on work ability.…”
Section: Discussionsupporting
confidence: 92%
“…Nowadays, WAI is commonly used worldwide for assessing work ability. WAI has also shown predictive value in the sense that a decreased WAI level increases the likelihood of premature retirement and death (2,3,4). However, multi-item measures such as WAI have disadvantages in terms of implementation, interpretation, and cost (5).…”
mentioning
confidence: 99%
“…First, we performed a multivariate analysis in which we also included trajectories of work ability in the regression model on retirement. Work ability is related to both work engagement (6)(7)(8) and (early) retirement (26,27), and in the present de Wind et al study we were primarily interested in the motivational process. Second, a multivariate analysis was performed only including persons in which there was agreement between intention to retire and actual retirement ("no intention and no retirement" or "intention and retirement").…”
Section: Discussionmentioning
confidence: 95%
“…Individual factors, health and fitness, lifestyle, and work demands are the strongest predictors of work ability (18)(19)(20). Earlier analyses based on a shorter follow-up of current data have shown that work ability declines from midlife onwards (21) and decreased work ability predicts work disability, spells of sickness absence, and early retirement from employment (22)(23)(24). Only little is known about the changes in work ability during retirement.…”
mentioning
confidence: 99%